COMMUTING TRACES OF SYMMETRIC LEFT BICENTRALIZER ON SEMIPRIME RINGS - H. Majeed, Abdhul Rahman; Mahmood, Auday Hekmat (MAGISTRA, 2015)
Let R be an associative ring. The purpose of this paper is to study the investigate identities satisfied by symmetric left Bicentralizer on a semiprime rings which make the trace of such mappings is commuting on R. Key words and phrases: Semiprime rings, symmetric left Bicentralizer, trace of biadditive mappings, commuting mapping.